Iliac bone graft for the treatment of bone loss and non-union of the distal radius.: A polytraumatized patient with an open Gustilo IIIB wrist fracture - Saracco, Michela; Merendi, Gianfranco; Rocchi, Lorenzo (Acta Biomedica Atenei Parmensis, 2023)
Background/Aim of the work: Open distal radius fractures are rare compared to closed ones. They mainly affect young people with high-energy trauma and are burdened with a high number of complications, including non-union. In this case report, we describe the technique used to manage bone loss and non-union of the distal radius of a polytraumatized patient with an open Gustilo IIIB fracture of the wrist.Case Report: 58-year-old man, suffering from head trauma and open right wrist fracture after motorcycle accident, underwent emergency damage control with debridement, antibiotic prophylaxis and stabilization in an external fixator. Then, he developed infection and bone loss, associated with an injury of the median nerve.  Non-union were treated with iliac crest bone graft, open reduction and internal fixation (ORIF).Outcomes: At the follow-up 6 months after the bone graft and ORIF procedure and 9 months after the trauma, the patient was clinically healed, with good performance status.Conclusions: Treatment of non-union in open distal radius fractures with iliac crest bone graft is a viable, safe and easy surgical choice.